Longer Course of Induction Chemotherapy Followed by Chemoradiation Favors Better Survival Outcomes for Patients With Locally Advanced Pancreatic Cancer. (February 2016) - Faisal, Farzana; Tsai, Hua-Ling; Blackford, Amanda; Olino, Kelly; Xia, Chang; De Jesus-Acosta, Ana; Le, Dung T.; Cosgrove, David; Azad, Nilofer; Rasheed, Zeshaan; Diaz, Luis A.; Donehower, Ross; et al.
Abstract : Objectives: At diagnosis, 30% of patients with pancreatic cancer are unresectable stage 3 locally advanced. The standard treatment for locally advanced pancreatic cancer (LAPC) is not defined. The current study was conducted to assess the roles of chemotherapy and chemoradiation for LAPC treatment. Materials and Methods: Between June 2006 and March 2011, 100 patients with LAPC were treated at the Johns Hopkins Hospital. Retrospective analysis was performed to compare cumulative incidence of progression (CIP) and overall survival (OS) among different subgroups. Results: For the 100 patients, the median OS was 15.8 months and the median CIP was 8.4 months. The combination of chemotherapy and chemoradiation before disease progression was significantly associated with improved CIP ( P =0.001) and improved OS when compared with chemoradiation alone (median OS: 16.4 vs. 11.1 mo, P =0.03). Among patients receiving combination treatment, patients who received chemotherapy first followed by chemoradiation had a trend toward lower CIP ( P =0.09) and improved OS (median OS: 18.1 vs. 11.0 mo, P =0.09). Patients who received >2 cycles of chemotherapy before chemoradiation had a significantly decreased CIP ( P =0.008) and a trend toward better OS (median OS: 19.4 vs. 15.7 mo, P =0.10). On multivariate analysis, receiving >2 cycles of chemotherapy before chemoradiation was associated with improved CIP. Conclusions: Although combination chemotherapy and chemoradiation is favored in the treatment of LAPC, longer induction chemotherapy may play a more important role in sensitization of tumors to subsequent chemoradiation. Our results support treating patients with induction chemotherapy for at least 3 cycles followed by consolidative chemoradiation. These results merit further validation by a prospective study.